Technology and information trust for supporting risky decisions based on social-media content - Nurse, J; Goldsmith, M; Creese, S; Lamberts, K (IEEE, 2015)
As the availability of open-source information online increases, there are growing concerns regarding its reliability. This has led to renewed emphasis in quality- and trust-metrics research within the social computing space, to assist individuals in determining how reliable pieces of information actually might be. In this article, we take a step back to rigorously investigate the utility of trustworthiness information support provided via computer and information technologies. Our research aim is to assess whether people can cognitively combine trustworthiness advice and evaluative content to make decisions, particularly in a risk-related context. Moreover, we analyse individuals’ ability to sensitise their decisions given that information and the criticality of a set task. The results suggest that individuals can perform well at both these tasks even when there are only subtle variations in information and advice. This empirically validated contribution provides a basis for a commonly-made assumption, and reinforces humans as efficient and effective information processors. The study also highlighted several social computing factors that may affect such decisions including quantity of content, existing trust relationships and reasoning behind trustworthiness advice.